Intratumoral delivery of mRNA encoding the endogenous TLR2/6 agonist UNE-C1 induces immunogenic cell death and enhances antitumor activity - Kim, Uijoo; Hwang, Sunkyo; Cho, Seongmin; Kim, Hyeong Yun; Ban, Hamin; Park, Joohee; Mun, Jeongwon; Kim, Nayoung; Suh, Ji Hun; Choi, Jihye; Shin, Yungyeong; Kim, Sang Bum; et al. (Frontiers in Immunology, 2024)
IntroductionRecent investigations have highlighted the intratumoral administration of Toll-like receptor (TLR) ligands as a promising approach to initiate localized immune responses and enhance antitumor immunity. However, the clinical application of these ligands is limited by their rapid dissemination from the tumor microenvironment, raising concerns about reduced effectiveness and systemic toxicity.MethodsTo address these challenges, our study focused on the intratumoral delivery of mRNA encoding UNE-C1, a TLR2/6 ligand known for its efficacy and low toxicity profile. We explored the potential of UNE-C1 to induce immunogenic cell death (ICD) through autocrine mechanisms, facilitated by the release of damage-associated molecular patterns (DAMPs) triggered by TLR2 activation.ResultsOur findings indicate that sensitivity to UNE-C1-induced cell death is dependent on the expression levels of TLR2 and the Fas-associated death domain (FADD) in cancer cells. Furthermore, we investigated the paracrine activation of dendritic cells (DCs) by UNE-C1 via TLR2 signaling, which primes a CD8+ T cell response essential for tumor regression.DiscussionOur results advocate for the intratumoral delivery of UNE-C1 via mRNA therapy as a promising strategy for innovative antitumor treatments.